1998
DOI: 10.1080/10641269891314249
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Review of Penaeus stylirostris

Abstract: Tropical species such as P. monodon, P. vannamei, and P. stylirostris were first considered as candidate species for aquaculture in early 1970s or around 25 years ago. At that time, the first nutrition studies began in laboratories using wild stock. Most labs were under pressure to find quick answers to the formulation of shrimp feeds. Feed manufacturers conducted a number of proprietary experiments. Shrimp nutritionists did not link their problems to those encountered with monogastrics and specific problems w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 15 publications
0
8
0
1
Order By: Relevance
“…1998), and F. merguiensis (Allan & Smith 1998). Litopenaeus stylirostris exhibits a decrease in protein requirement according to age from 44% crude protein for post‐larvae of 7–15 mg to 30% for juveniles (Cuzon & Aquacop 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1998), and F. merguiensis (Allan & Smith 1998). Litopenaeus stylirostris exhibits a decrease in protein requirement according to age from 44% crude protein for post‐larvae of 7–15 mg to 30% for juveniles (Cuzon & Aquacop 1998).…”
Section: Discussionmentioning
confidence: 99%
“…For shrimp, there are few data available on the optimum P/E ratio using a native protein source as used in the present study. This type of protein source has been recommended by several workers who evaluated the quality of proteins that should be used in shrimp feeds (Cousin 1995; Cuzon & Aquacop 1998; Ricque‐Marie et al . 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Celite (Sigma ® , Sigma‐Aldrich Quimica S. A., Toluca, Mexico) was used as a marker and apparent digestible content (ADC) for dry matter ( DM ) and protein ( P ) was measured (Cuzon & Aquacop ): ADCDM(%)=100×[100(%marker in diet/%marker in faeces) ADCP(%)=100×[100(%marker in diet/%marker in faeces)×(%nutrient in faeces/%nutrient in diet)]. …”
Section: Methodsmentioning
confidence: 99%
“…Celite (Sigma ® , Sigma-Aldrich Quimica S. A., Toluca, Mexico) was used as a marker and apparent digestible content (ADC) for dry matter ( DM ) and protein ( P ) was measured (Cuzon & Aquacop 1998):…”
Section: Experimental Designmentioning
confidence: 99%
“…Constant improvements through nutritional research have narrowed the dependency on live feeds and some studies have reported on the successful total replacement of microalgae and/or Artemia at different larval stages (Kanazawa, 1990;Cuzon and Aquacop, 1998;D'Abramo et al, 2006). Complete replacement of live foods with formulated diets through all the larval stages has also been demonstrated (Jones et al, 1979;Kurmaly et al, 1989;Le Vay et al, 1993) but while survival can be equivalent to that of larvae reared on live foods, growth and development may be slower (Le Vay et al, 1993;D'Abramo et al, 2006).…”
Section: Introductionmentioning
confidence: 99%